Factors associated with colonization of Streptococcus mutans in 8‐ to 32‐month‐old children: a cohort study. (December 2013) - Zhou, Y; Yang, JY; Zhi, QH; Tao, Y; Qiu, RM; Lin, HC
Abstract Background The factors involved in Streptococcus mutans colonization in young children are not clear. The aim of this study was to determine the factors associated with S. mutans colonization in 8‐ to 32‐month‐old children. Methods A group of 225 caries‐free 8‐month‐old children was recruited for the study. They were examined every six months until they were 32 months old to investigate their environmental factors, host factors and bacterial transmission factors. At baseline and during each examination, their teeth were checked for the presence of dental plaque and developmental defects of enamel, and S. mutans plaque status was assessed using a real‐time PCR test. Results Eight children (3.6%) showed S. mutans colonization by the age of 8 months. The percentages of colonization were 6.0% at 14 months, 16.2% at 20 months, 26.7% at 26 months, and 33.5% at 32 months. The results showed that females (p = 0.006), children with enamel hypoplasia (p = 0.024), children with low birth weights (p = 0.005), those who consume more sweets (p < 0.001), and those with a higher proportion of visible plaque (p = 0.020 and p = 0.041) were more likely to be colonized by S. mutans. Conclusions Streptococcus mutans colonization in young children was associated with gender, tooth enamel hypoplasia, low birth weight, frequent consumption of sweets and poor oral hygiene.